Combining ability analysis for grain yield and its components in malt barley (Hordeum vulgare) - SINGH, BALJIT; SHARMA, ACHLA; JOSHI, NEHA; MITTAL, P; SINGH, SARVJEET (The Indian Journal of Agricultural Sciences, 2013)
Combining ability analysis in barley (Hordeum vulgare L.) involving seven diverse elite lines suitable for malting and their 21 F1s generated in half diallel fashion, indicated significant differences among the genotypes for all the seven traits studied. Analysis of variance for combining ability revealed that variances due to gca as well as sca were highly significant for different traits except spike length. The preponderance of non-additive gene effects for grain yield and of additive gene effects for yield components were detected. Based on the estimates of gca effects, good general combiners were identified for different traits. Similarly based on sca effects, desirable specific combiners were identified. It was noted that good specific combiners did not necessarily involve good general combiners.